Eat1-Like Alcohol Acyl Transferases From Yeasts Have High Alcoholysis and Thiolysis Activity - Patinios, Constantinos; Lanza, Lucrezia; Corino, Inge; Franssen, Maurice C. R.; Van der Oost, John; Weusthuis, Ruud A.; Kengen, Servé W. M. (Frontiers in Microbiology, 2020)
Esters are important flavor and fragrance compounds that are present in many food and beverage products. Many of these esters are produced by yeasts and bacteria during fermentation. Whilst ester production in yeasts through the alcohol acyl transferase reaction has been thoroughly investigated, ester production through alcoholysis has been completely neglected. Here, we further analyze the catalytic capacity of the yeast Eat1 enzyme and demonstrate that it also has alcoholysis and thiolysis activities. Eat1 can perform alcoholysis in an aqueous environment in vitro, accepting a wide range of alcohols (C2-C10) but only a small range of acyl donors (C2-C4). We show that alcoholysis occurs in vivo in several Crabtree negative yeast species but also in engineered Saccharomyces cerevisiae strains that overexpress Eat1 homologs. The alcoholysis activity of Eat1 was also used to upgrade ethyl esters to butyl esters in vivo by overexpressing Eat1 in Clostridium beijerinckii. Approximately 17 mM of butyl acetate and 0.3 mM of butyl butyrate could be produced following our approach. Remarkably, the in vitro alcoholysis activity is 445 times higher than the previously described alcohol acyl transferase activity. Thus, alcoholysis is likely to affect the ester generation, both quantitatively and qualitatively, in food and beverage production processes. Moreover, mastering the alcoholysis activity of Eat1 may give rise to the production of novel food and beverage products.